Artes plásticas y el desarrollo emocional en los estudiantes de la Institución Educativa Inicial N°672 San Juan Bautista 2024 - Muñoz Alvan, Mary Liseth (2025)
The main objective of this research was to explore the existence of a relationship between the practice of plastic arts and the emotional development of students at the Initial Educational Institution No. 672 San Juan Bautista in 2024. The study followed a quantitative approach under a non-experimental, correlational methodological design. The sample consisted of 72 students from the aforementioned institution. To collect the data, the direct observation technique was applied using a specifically designed guide, which was validated by experts in the educational field. The results, calculated using Spearman’s Rho coefficient, yielded a value of r = 0.747, indicating a positive correlation of moderate to strong intensity between the two research variables, with a statistical significance level of p = .05. These findings confirmed the existence of a statistically significant relationship between plastic arts and the emotional development of the observed students. Furthermore, the alternative hypothesis was rejected, and the general hypothesis of the study was confirmed. In summary, it was concluded that engagement in plastic art activities is significantly related to the strengthening of emotional development in children at the Initial Educational Institution No. 672 San Juan Bautista.